Fenomena Teman Ahok Menghangatkan Politik Partai - Ritaudin, M. Sidi (JURNAL TAPIS, 2016)
"Booming" Ahok phenomenon and Friends Ahok had atumultuous world of Indonesian politics. He did not haveany support political parties or civil society organizations.This is a political anomaly, he dared to openly oppose thelegislature to expose corruption in parliament. Ordinarypoliteness norms donot apply to Ahok. For him, there wasno politeness that should be shown in front of people whoconsiders hoodlums and robbers public money. Accordingto Basuki Tjahaya Purnama (Ahok), anger is "politeness"for people who are considered evil. In his nomination, hechose the path of non-party independent and has thesupport of the Friends Ahok reached 98.5 percent andAhok elektabilitas rate to 59 percent. Really Ahok is apolitical anomaly Indonesia. Political Party principles andmay have different political views. Political parties arebuilt to facilitate the struggle for power that the cake laterdivided by the officials and political supporters. Theyestablish the rules and laws that are sometimes not neededby the people, or even contrary to the interests of thepeople. They were squaring himself as a political,prospective rulers, officials, owners of the country and sothat deprive their own sense of reason that they were bornof the people. Issues “deparpolization” actually veryinteresting because itis time for political parties to reflecton the achievements and behavior itself so no longerpossible Indonesian people are aware that they needpeople who emerged from the churning that is located no in the political parties, but emerged from hell sufferingpeople , If Ahok and Friends Ahok choose an independentpath that too is a legitimate option and there are laws thatAct No. 8 of 2015 on the Amendment of the Stipulation ofGovernment Regulation in Lieu of Law No. 1 of 2015concerning the election of Governor, Regent, and Mayorbe Constitution. Although it does not belong to a party buthas a clear direction that reason and conscience.